2020
DOI: 10.3982/ecta15505
|View full text |Cite
|
Sign up to set email alerts
|

Age of Marriage, Weather Shocks, and the Direction of Marriage Payments

Abstract: We study how aggregate economic conditions affect the timing of marriage, and particularly child marriage, in Sub‐Saharan Africa and in India. In both regions, substantial monetary or in‐kind transfers occur with marriage: bride price across Sub‐Saharan Africa and dowry in India. In a simple equilibrium model of the marriage market in which parents choose when their children marry, income shocks affect the age of marriage because marriage payments are a source of consumption smoothing, particularly for a woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 100 publications
(105 reference statements)
5
73
0
3
Order By: Relevance
“…5 In this paper, I develop a different approach to test for wage rigidity: I isolate shocks to the marginal revenue product of labor, and examine wage adjustment and employment effects in response to these shocks. 6 I apply this approach in the context of markets for casual daily agricultural labor, a major source of employment in poor countries. In this setting, local rainfall variation generates transitory labor demand shocks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 In this paper, I develop a different approach to test for wage rigidity: I isolate shocks to the marginal revenue product of labor, and examine wage adjustment and employment effects in response to these shocks. 6 I apply this approach in the context of markets for casual daily agricultural labor, a major source of employment in poor countries. In this setting, local rainfall variation generates transitory labor demand shocks.…”
mentioning
confidence: 99%
“…There remains a debate as to whether wage rigidity has any relevance for employment dynamics (e.g., Pissarides 2009, Elsby 2009, Rogerson and Shimer 2011, Schmitt-Grohé and Uribe 2013). 6 Holzer and Montgomery (1993) perform analysis in this spirit. They assume sales growth reflects demand shifts, and examine correlations of wage and employment growth with sales growth in the United States.…”
mentioning
confidence: 99%
“…73 Second, economic empowerment programmes may be a crucial strategy for securing women's and girls' livelihoods in emergency settings. The impact of such programmes can go beyond economic aspects and may also decrease the risk of harmful coping behaviours such as marrying off a young daughter to receive a bride-price, 33 selling productive assets 74 or engaging in risky sexual behaviour. 75 One of the most widely used and promising tools to cushion the economic shock induced by a PHE are unconditional cash transfers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Corno and colleagues found that in sub-Saharan Africa, girls aged 12-17 years had a significantly higher likelihood of getting married if their household was affected by a drought. 33 In addition, in high-income and low-income countries alike, women may face an increased informal care burden in the context of PHEs, either to look after family members who need daily assistance or who have fallen sick, 34 or to look after their children, 35 as was the case during the COVID-19 lockdowns. 4 Increased care responsibility can thwart women's employment opportunities and amplify pre-existing biases in couples' division of paid and unpaid work.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Rainfall data have been used to estimate the consequences of weather shocks at the time of birth on adult health, education and socio-economic outcomes [ 18 ], HIV rates [ 19 ], child health [ 20 ] and educational attainment [ 21 ], amongst others. In Sub-Saharan Africa and India, a study employed Demographic Household Surveys and rainfall data to look at the implications of weather shocks on the timing of marriage and found that the age of marriage responds to the short-term changes in the aggregate economic conditions caused by weather shocks, though with differential impact directions depending on regional dowry or bride price practices [ 22 ].…”
Section: Introductionmentioning
confidence: 99%